The incidence Breast cancer of in eastern Libya - Mohamed, Hammad Assanussi (faculty of Basic Medical Science - Libyan International Medical University, 2018)
The aim of this study is to show the incidence of breast cancer in 2017 in Eastern of libya and compared with studies in 2003 &2012 further more, the most predominant age group & the most common risk factors of breast cancer that associated with Libyan people . A data was collected from the oncology department in BMC. Using random collecting methods to cover a proportion of breast cancer in Eastern Libya. We acknowledge the oncology department in Benghazi Medical Center (BMC) for allowed to access files . We very grateful to Dr. Rehab Shambash for data analysis. And we thank Sanad Hamed & Mohamed Hussein for helping collecting data. The incidence of breast cancer in Eastern of libya in 2017 was increased by 7.2% between 2012-2017 .Also the incidence in 2017 compared with 2003 Dramatically increased by 23.5 % . Based on that we can say the incidence of breast cancer is more higher in 2017 due to the risk factors that will be mentioned below , overall lack of education , awareness and knowledge plays an important role in breast cancer .
Breast cancer is cancer that develops from breast tissue.[9] Signs of breast cancer may include a lump in the breast, a change in breast shape, dimpling of the skin, fluid coming from the nipple, a newly inverted nipple, or a red or scaly patch of skin.[1][2] In those with distant spread of the disease, there may be bone pain, swollen lymph nodes, shortness of breath, or yellow skin. Breast Cancer is an important health concern in Libya, especially in the setting of an aging population and limited healthcare facilities. Cancer is a group of diseases involving abnormal cell growth with the potential to invade or spread to other parts of the body